The occupational stress affects the health conditions of military police officers El estrés laboral afecta las condiciones de salud de los oficiales de la policía militar - Schlichting Junior A.M.* (2014)
© 2014, Editorial Ciencias Medicas. All Rights reserved.Introduction: the agents who are responsible for the public security are exposed to working conditions that affect quality of life, sspecially the stress that these professionals daily experience.Objective: to describe the socio-demographic and occupational characteristics, the health conditions and the occupational stress indicators of the of military officers from the State of Santa Catarina. Methods: descriptive correlational study with a sample of 1069 subjects, 583 police officers in qualifying course (QMO) and 486 qualified officers. The Short Form Health Survey and Occupational Stress Indicators were applied.Results: the results showed that the scores of health conditions were below the cut off for both the physical and the mental components. The vitality variable (p=.000), social functioning (p=.017), age (p=.018) and number of hours worked per day (p=.023) showed a significant association with occupational stress score.Conclusions: it is concluded that there are significant differences between health indicators and occupational stress. The tendency to reduction of vitality caused by occupational stress and the social function increases with the age and with higher number of workhours per day.